Verba Bahasa Banjar Dialek Banjar Hulu Kecamatan Tembilahan Kota - Fajrizka, Oklidia; Alber, Alber (Jurnal Sastra Indonesia, 2023)
Language is an ability that humans have with other humans by using signs, for example gestures and words. Language has an important role in human life, because with the existence of language a culture will be achieved in the midst of society. Based on the Banjar Hulu dialect verbs, the problem can be formulated: (1) What is the form of the verbs in the Banjar Hulu dialect, Tembilahan Kota District? The aims of this study are: (1) To describe the forms of verbs in the Banjar language, Banjar Hulu dialect, Tembilahan Kota district. The information and data collected is described and analyzed. The author uses Alwi's supporting theory, et al (2010), and several other supporting theories. The population of this research is the Verbs of the Banjar Language, Banjar Hulu Dialect, Tembilahan City District. The method used is the method in this research is descriptive method. This study concluded that there were 37 which were divided into original verbs and derived verbs. There are 4 prefixes found after doing the analysis, namely maN-, ba-, ka-, ta. Found 3 suffixes namely -an, -kan, -I, as well 3 confixes maN-i, ba-an, and ta-an. The Banjar and Indonesian language systems largely influence each other. This is evidenced by the discovery of several vocabularies that have overall morphological similarities. Kata Kunci: morphology, verb, Banjar language